2007
DOI: 10.1007/s00268-007-9111-6
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal Colectomy with Antiperistaltic Cecorectal Anastomosis in the Treatment of Slow‐transit Constipation: Long‐term Impact on Quality of Life

Abstract: Comparing our results to those of the most homogeneous literature data, SCCA does not appear to be inferior to subtotal colectomy with ileorectal anastomosis (IRA) in terms of therapeutic effectiveness, postoperative mortality and morbidity, or overall impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 24 publications
2
55
0
3
Order By: Relevance
“…Subtotal colectomy with antiperistaltic cecorectal anastomosis (SCCRA) seems to provide a valid alternative to total colectomy with ileorectal anastomosis (IRA), the most widely adopted procedure for slow-transit constipation, with potentially less functional impairment [5][6][7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…Subtotal colectomy with antiperistaltic cecorectal anastomosis (SCCRA) seems to provide a valid alternative to total colectomy with ileorectal anastomosis (IRA), the most widely adopted procedure for slow-transit constipation, with potentially less functional impairment [5][6][7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…At present, most scholars advocate such surgery. Marchesi et al [14] performed subtotal colectomy and cecocolostomy for 22 patients with colonic slow-transit constipation and reported a postoperative complication incidence rate of 9.1 %, an average Wexner continence score reduced from 20.3 before the surgery to 2.6 after the surgery, an average postoperative GIQLI of 115.5 (125.8 for health people), and a satisfaction rate of 88.2 % with the surgery. Sarli et al [15] reported 10 patients who underwent subtotal colectomy and cecorectal antiperistaltic anastomosis and obtained a constipation remission rate of 100 %; average frequency of defecation was increased from once every 10 days before the surgery to 2.…”
Section: Subtotal Colectomy and Ascending Colon (Or Cecum)-rectum Anamentioning
confidence: 97%
“…Zudem werden auch zunehmend retrospektive Analysen zur anisoperistaltischen caecorektalen Anastomose veröffentlicht [26][27][28]. Hier müssen jedoch die Langzeitergebnisse noch abgewartet werden.…”
Section: Antegrader Koloneinlaufunclassified